Numerical Investigation on Heat Transfer and Pressure Drop in Silver/Water Nanofluids Flowing Through Tubes with Variable Expansion–Contraction Ratios - Enio Pedone Bandarra Filho; Erick Oliveira do Nascimento; Muhammad Farooq; Luben Cabezas-Gómez (Energies)
This study presents a numerical investigation on the heat transfer and pressure drop characteristics of silver/water nanofluids (0.1–0.5 vol.%) flowing in tubes with four distinct expansion–contraction ratios (ECR = 1.25, 1.50, 1.75, and 2). Additionally, the impact of the distance between expansion and contraction (DEC) within the tubes was examined. The analysis was conducted under turbulent flow conditions and three-dimensional thermal convection in tubes subjected to a constant heat flux of 20 kW/m2, with the inlet Reynolds number maintained at approximately 20,000. The nanofluids were considered as single-phase and modeled in the Ansys Fluent 16 software through the finite volume method, and the equations were discretized through the second-order upwind scheme. The nanofluids demonstrated significant potential in enhancing thermal performance, particularly in tubes where the convective heat transfer coefficient was affected by abrupt expansion–contraction ratio (ECR). A maximum increase of up to 24.90% in the average convective heat transfer coefficient compared to the base fluid was observed. Exergy efficiency showed a tendency to increase by up to 29.97% with the use of nanofluids. The findings indicate that the convective heat transfer coefficient can both increase and decrease with the expansion–contraction ratio (ECR) of the tube, as can the pressure drop. Consequently, the application of this passive technique, incorporating silver/water nanofluids, holds promise for use in cooling systems, nuclear reactors, and other similar applications, provided they are meticulously designed.